Field evaluation of the sex pheromone of the cacao pod borer (Conopomorpha cramerella Snellen) in the Philippines - Amalin, Divina M.; Arcelo, Mercedes; Almarinez, Billy Joel M.; Castillo, Rhodina C.; Legaspi, Jesusa C.; Santos, Kris Lord T.; Tavera, Mary Angelique A.; Janairo, Jose Isagani B.; Zhang, Aijun (Frontiers in Agronomy, 2023)
Cacao is a promising high-value crop in the Philippines and considered one of the key players globally in providing the raw materials for chocolate making. But, before the Philippines can take this market opportunity, production constraints from various pests should be addressed. The cacao pod borer (CPB), Conopomorpha cramerella, is one of the major insect pests of cacao in the Philippines, which can cause up to 50% annual loss or even higher if proper management is not employed. Management of CPB heavily relies on chemical control but is becoming unpopular because of its high cost and risks to humans and the environment. A number of efforts have been done to develop sex pheromones for monitoring and control of CPB. Field bioassay of the new blend of CPB sex pheromones was conducted in southern Philippines to determine its efficiency and identify the appropriate trap height placement in a cacao field which is important in maximizing the efficiency of the sex pheromone traps for inclusion in the integrated pest management (IPM) program of CPB. Pheromone lures at four different trap heights (1.0 m, 0.5 m above the canopy, 0.0 m or along the canopy, and 0.5 m below the canopy), and a blank lure (control) placed 1.0 m above the canopy were evaluated in terms of male CPB trap catches. Results showed significantly higher male CPB trap catches when installed at least 0.5 m above the canopy while minimal to zero male CPB catches were obtained from the control traps with blank lure confirming the attractiveness of the new blend of the CPB sex pheromone in the field. This suggests the reliability of the pheromone-based method for monitoring and control of CPB and as a major component of the IPM program.